PENGURANGAN KETIDAKPASTIAN MELALUI KOMUNIKASI INTERPERSONAL REMAJA PANTI ASUHAN (STUDI PADA REMAJA PPSA â€œWORO WILOSOâ€ SALATIGA) - Zuhriah, Ana (Jurnal Common, 2019)
People as a creature that has a fairly high mobility in an effort to meet the needs of inevitably will adjust to the different social environment. This environment will certainly make someone encountering a new situation which is full of uncertainty in which the man claimed to communicate with interpesonal as an attempt to obtain information as to the existence of his/her life, including adolescents in Panti Pelayanan Sosial Anak Woro Wiloso Salatiga. A sense of uncertainty in adolescents who live in orphanage care must be reduced so that they are able to survive and continue their education through a orphanage provided by the government. The purpose of this research is to know the uncertainty as well as the process and strategy of adolescent in reducing uncertainty. This research is a descriptive qualitative study type where the data was collected through interviews with 6 people the informant i.e. adolescents of PPSA Woro Wiloso Salatiga aged 13-18 years. The results showed that adolescent in the orphanage have the cognitive uncertainty and behavioral uncertainty, they apply the reduction processes and uncertainty reduction strategies through interpersonal communication on the early days of interacting in the orphanage. Keywords:adolescents,orphanage,uncertainty reduction theory, interpersonal communication